International experience of adaptation and application of digital ecosystems by industrial enterprises and clusters - Babkin Alexander; Tashenova Larissa; Mamrayeva Dinara; Kulzhambekova Barno; Yormatov Ilmidin (BIO Web of Conferences)
This article is dedicated to exploring the theoretical aspects of forming and managing digital ecosystems in industrial enterprises; the main advantages of implementing digital ecosystems in organizational activities and their distinctive features compared to customized digital ecosystems are also examined. The integrated use of digital technologies, digital platforms, and ecosystems enables efficient resource management, enhances labor productivity, and improves key performance indicators. Drawing on thematic and scholarly research, the article analyzes key strategic plans for the formation of digital ecosystems to enhance competitiveness and foster innovation in the industrial sector of leading foreign countries such as the United States, Germany, Japan, and China. The relevance and keen interest of these countries in studying the aspects of forming and implementing digital ecosystems in industrial enterprises for government and scientific organizations funding such research are noted. The article presents business cases on digitization and the development of digital ecosystems in the machine-building industry, using examples from American company “Tesla”, French railway company “Alstom”, and the nuclear industry, exemplified by the Russian State Atomic Energy Corporation “Rosatom”.